The Influence of Gender Based Violence on Women Empowerment in Kimyendde Sub-county, Mukono District - Yunia Kiweewa (Uganda Christian University, 2024)
Gender based violence in all its all types has led to limitation of women empowerment in kimenyedde sub county and globally. This has resulted into high dependence of women limited access of women in decision making and political participation and pursing career goals resulting to cases of increased submission to male decision making by women, limiting girl child education, limited representation of women’s needs, high rated of violence against adult women. Recognizing all this, this study seeks to increase the awareness of this women suppression by university students, the factors causing this problem, and developing different strategies that can address the occurrence of this problem. This research is structured as follows: Chapter One that provides a detailed background ,the objectives, etc. Chapter Two provides a literature review of the existing academic literature of Gender Based Violence on women empowerment, Chapter 3 contains the methodology, the different methods of data collection ,analysis. Chapter 4 presents the findings after exploring the occurrence of Gender Based Violence on women empowerment outlining the key factors that lead to this problem. The final one is Chapter 5 which the different comprises conclusions and recommendations after the analysis of the data.
Undergraduate research